Effect of stress path on the mechanical properties of calcareous sand - Wei, Houzhen; Liu, Hao; Li, Xiaoxiao; Tao, Zhao; Wu, Yongjie; Shen, Jianhua; Yin, Mei (Underground space (Beijing), 2023)
Calcareous sand is widely observed in the foundation of off-shore infrastructure. Although a lot of research has been carried out on the mechanical properties of calcareous sand, study into the influence of the stress–strain path on the mechanical behaviour of calcareous sand is very limited. In this study, a series of triaxial tests were performed on calcareous sand under three different stress paths. The particle morphology of calcareous sand before and after the tests, the stress–strain relationship under different stress paths, and the characteristics of shear strength and deformation were investigated. The results show that the consolidation pressure and stress path have significant effects on the volume strain, strength, and particle breakage of calcareous sand. In addition, the underlying mechanisms of the different behaviours of calcareous sand observed in this study were discussed.